Somatostatin receptor 2A in gliomas: Association with oligodendrogliomas and favourable outcome - Kiviniemi A; Gardberg M; Kivinen K; Posti JP; Vuorinen V; Sipila J; Rahi M; Sankinen M; Minn H (IMPACT JOURNALS LLC, 2022)
Somatostatin receptor subtype 2A (SSTR2A) is a potential therapeutic target in gliomas. Data on SSTR2A expression in different glioma entities, however, is particularly conflicting. Our objective was to characterize SSTR2A status and explore its impact on survival in gliomas classified according to the specific molecular signatures of the updated WHO classification. In total, 184 glioma samples were retrospectively analyzed for SSTR2A expression using immunohistochemistry with monoclonal antibody UMB-1. Double staining with CD68 was used to exclude microglia and macrophages from analyses. SSTR2A staining intensity and its localization in tumor cells was evaluated and correlated with glioma entities and survival. Diagnoses included 101 glioblastomas (93 isocitrate dehydrogenase (IDH) -wildtype, 3 IDH-mutant, 5 not otherwise specified (NOS)), 60 astrocytomas (22 IDH-wildtype, 37 IDH-mutant, 1 NOS), and 23 oligodendrogliomas (19 IDH-mutant and 1p/19q-codeleted, 4 NOS). SSTR2A expression significantly associated with oligodendrogliomas (79% SSTR2A positive) compared to IDH-mutant or IDH-wildtype astrocytomas (27% and 23% SSTR2A positive, respectively), and especially glioblastomas of which only 13% were SSTR2A positive (p < 0.001, Fisher's exact test). The staining pattern in glioblastomas was patchy whereas more homogeneous membranous and cytoplasmic staining was detected in oligodendrogliomas. Positive SSTR2A was related to longer overall survival in grade II and III gliomas (HR 2.7, CI 1.2-5.8, p = 0.013). In conclusion, SSTR2A expression is infrequent in astrocytomas and negative in the majority of glioblastomas where it is of no prognostic significance. In contrast, oligodendrogliomas show intense membranous and cytoplasmic SSTR2A expression, which carries potential diagnostic, prognostic, and therapeutic value.